PERCEPTIONS AND INTERESTS OF IBA UNIVERSITY FACULTY OF AGRICULTURE STUDENTS IN CONTINUING BUSINESS IN AGRICULTURE (Sylva : Jurnal Penelitian Ilmu-Ilmu Kehutanan, 2022)
This study aims to identify the perceptions and interest of students of the Faculty of Agriculture, University of IBA Palembang in continuing their business in agriculture and to find out how the relationship between perceptions and interests of students of the Faculty of Agriculture IBA Palembang University in continuing its business in agriculture. The selection of the location at the Faculty of Agriculture, University of IBA Palembang was done intentionally (purposive sampling). Data collection in the field was carried out in January – May 2022. The results obtained by this study were concluded, namely: 1) The perception score of the students of the Faculty of Agriculture, University of IBA has an average score of 45.88 and lies in the positive criteria, from the three perception indicators, the knowledge indicator and the family environment indicator has high criteria (positive), while the experience indicator has medium criteria. 2) Interest scores of students from the Faculty of Agriculture, University of IBA have an average score of 62.95 which is located on the high criteria, the interest indicators consisting of indicators of interest, enthusiasm, involvement and desire are on the high criteria (interested, enthusiastic, involved, and willing), while indicators of pleasure are in the criteria of being quite happy. 3) Students' perceptions of the Faculty of Agriculture, University of IBA have a real and very strong correlation with the interests of students of the Faculty of Agriculture, University of IBA, especially for indicators of knowledge and family environment